Estimation of changes in C-reactive protein level and pregnancy outcome after nonsurgical supportive periodontal therapy in women affected with periodontitis in a rural set up of India - Mayur S Khairnar; Babita R Pawar; Pramod P Marawar; Darshana M Khairnar (Wolters Kluwer Medknow Publications, 2015)
Aims and Objectives: Estimation of changes in C-reactive protein (CRP) level and pregnancy outcome after nonsurgical supportive periodontal therapy in pregnant women affected with Periodontitis. Materials and Methods: A total of 100 pregnant females with periodontitis were assigned to treatment and control groups. All the details about previous and current pregnancies were obtained. Full-mouth periodontal examination was done at baseline, which included oral hygiene index simplified plaque index, gingival index, and clinical attachment loss. CRP level was also measured from collected blood sample initially at baseline and later after the delivery in both the group. Subjects in the treatment group received nonsurgical periodontal treatment during the second trimester of gestational period, and those in the control group did not receive any periodontal therapy during this period. Periodontal therapy included mechanical plaque control instructions and scaling and root planning. Outcome measures assessed were changes in CRP levels, gestational age, and birth weight of the infants. When delivery occurred at <37 weeks of gestation, it was considered as preterm birth (PTB), and low birth weight (LBW) was recorded when the infant weighed <2500 g. Results: In the treatment group, 32% of PTB and 68% of Normal term birth (NTB) delivery whereas in the control group 72% PTB and 28% of NTB were recorded. Infants measured with LBW were 36% in the treatment group and 52% in the control group. Mean birth weight was 2644.44 ± 450.53 g in the treatment group and 2447.82 ± 368.02 g in the control group (P < 0.05). Mean gestational age in the treatment group was 35.57 ± 2.40 weeks and 34.17 ± 2.92 weeks in the control group (P < 0.05). The treatment group showed statistically significant reduction in mean values of CRP level after delivery in comparison to baseline values (P < 0.05), whereas control group showed no significant reduction in values (P > 0.05). Conclusion: Nonsurgical supportive periodontal therapy may lower the risk of preterm delivery in females affected with periodontitis by reducing CRP level.